Ferroptosis-related genes in preeclampsia: integrative bioinformatics analysis, experimental validation and drug prediction - Lidan He; Feng Zhan; Xuemei Li; Huijuan Yang; Jianbo Wu (BMC Pregnancy and Childbirth)
Abstract Introduction Preeclampsia (PE) is a severe pregnancy complication with limited early diagnostic and therapeutic options. Ferroptosis, an iron-dependent cell death pathway, has emerged as a potential mechanism in PE pathogenesis. This study investigated ferroptosis-related genes (FRGs) in PE to identify diagnostic biomarkers and therapeutic targets. Methods Differentially expressed genes were identified from GEO databases and intersected with FRGs. Hub genes were selected using RandomForest and LASSO algorithms. Their diagnostic potential was evaluated through ROC analysis. Regulatory networks were constructed using transcription factors, microRNAs and potential drug targets. Hub gene expression was validated through immunohistochemistry, Western blot, and RT-qPCR in placental tissues and hypoxic trophoblasts. Results We identified 25 ferroptosis-related differentially expressed genes enriched in ferroptosis and HIF-1 pathways. Four hub genes (NDRG1, P4HA1, LDHA, and IDO1) showed high diagnostic efficiency (AUC=0.9182). Immune cell analysis revealed altered levels of plasma cells, CD8+ T cells, Tregs, monocytes, and M2 macrophages in PE, correlating significantly with hub gene expression. We identified 84 mRNA-miRNA and 119 mRNA-TF interactions. Among 19 potential drugs, Tetrahydro-NAD showed promising targeting potential. Experimental validation confirmed elevated expression of NDRG1, P4HA1, and LDHA, and decreased IDO1 in PE tissues and hypoxic conditions. Discussion This study identified four FRGs as potential PE biomarkers and therapeutic targets, providing new insights into PE pathogenesis through integrated bioinformatics and experimental validation. These findings may facilitate early PE diagnosis and treatment development.